A single dose vaccination with an elastase-dependent H1N1 live attenuated swine influenza virus protects pigs from challenge with 2009 pandemic H1N1 virus - Mašić Aleksandar (Sciendo, 2014)
The 2009 outbreak of H1N1 influenza A viruses in humans underscored the importance of pigs in influenza A virus evolution and the emergence of novel viruses with pandemic potential. In addition, influenza A virus infections continued to cause production losses in the agricultural industry resulting in a significant drop of profit. The primary method to control influenza A virus infections in pigs is through vaccination. Previously we demonstrated that two doses of an elastase-dependent live attenuated swine influenza virus administered by either the intratracheal or intranasal route can provide a high degree of protection in pigs against challenge with both homologous and different heterologous swine influenza viruses. Here we report the protection efficacy of a single dose elastase-dependent live attenuated swine influenza virus administered by the intranasal route against challenge with homologous subtypic H1N1 2009 pandemic swine-like influenza virus. Protection was observed in the absence of neutralizing antibodies specific for H1N1 2009 in sera.